2022
DOI: 10.1093/brain/awac147
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity of pain sensitivity in humans

Abstract: Pain intensity has been reported to fluctuate during the day in some experimental and clinical conditions, but the mechanisms underlying these fluctuations are unknown. Although the circadian timing system is known to regulate a wide range of physiological functions, its implication in pain regulation is largely unknown. Using highly controlled laboratory constant-routine conditions, we show that pain sensitivity is rhythmic over the 24 h and strongly controlled by the endogenous circadian timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 79 publications
2
34
0
Order By: Relevance
“…This can be attributed to the reduction of inflammatory mediators within the periodontal ligament post-activation of the archwire. This gradual reduction within the day is probably not a temporal observation of circadian effects [50,51] within the day, but rather the effect of greater amounts of time having elapsed in the evening since the original archwire activation and is consistent with other studies [43,52,53].…”
Section: Results In Contextsupporting
confidence: 90%
“…This can be attributed to the reduction of inflammatory mediators within the periodontal ligament post-activation of the archwire. This gradual reduction within the day is probably not a temporal observation of circadian effects [50,51] within the day, but rather the effect of greater amounts of time having elapsed in the evening since the original archwire activation and is consistent with other studies [43,52,53].…”
Section: Results In Contextsupporting
confidence: 90%
“…Pressure at this site is gradually increased at a steady rate (0.5 kg/sec) and stopped when the subject indicates the stimulus is first perceived as painful. A circadian rhythm in pain sensitivity has recently been established ( 53 ). Responses to painful stimuli could have relevancy for many military and civilian scenarios (e.g., injuries, post-surgical pain, chronic pain ( 54 ).…”
Section: Methodsmentioning
confidence: 99%
“…A major study was recently published to demonstrate the circadian nature of pain behavior in humans ( Daguet et al, 2022 ), although only data on men were reported. The participants were held in a constant routine protocol that prevented photic environmental cues from entraining or masking behavior.…”
Section: Circadian Rhythms Of Pain Behavior and Pain Sensitivitymentioning
confidence: 99%
“…Importantly, the authors were able to determine that the circadian system was the primary driving force of pain sensitivity rhythms. Homeostatic sleep pressure contributed to the rhythms, but only accounted for 20% of the rhythmicity ( Daguet et al, 2022 ). The observed rhythmicity and rhythmic shape observed in this study are supported by previous models ( Hagenauer et al, 2017 ) and other human studies examining pain threshold variations in humans outside of constant condition protocols ( Zhu et al, 2022 ).…”
Section: Circadian Rhythms Of Pain Behavior and Pain Sensitivitymentioning
confidence: 99%